IMPACT OF MICRO CREDIT ON REGIONAL ECONOMY : THE CASE OF PEOPLE BUSINESS CREDIT (KUR) IN YOGYAKARTA PROVINCE - Solikin, Akhmad; Prabowo, Sakti; Akhmadi, M Heru (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2025)
Micro, Small, and Medium Enterprises (MSMEs) are very important for Indonesian economy. However, numerous obstacles prevent MSMEs development, including capital. To overcome the obstacle, Indonesian government launched Small or People Business Credit (PBC) or Kredit Usaha Rakyat (KUR). This article aims at analyzing PBC toward regional sectoral economy. This research uses Interregional Input-Output Table approach by using Interregional Input-Output Table of 2016, which is the most update table available. Shock data used was contract value of KUR in Province of Yogyakarta Special Region. The results show that the majority impacts of KUR disbursements are accrued by economic sectors in Yogyakarta Province, especially sectors of Wholesale and Retails, Car and Motorcycle Reparation; Agriculture, Forestry and Fishery; Manufacturing Industry; and Other Services. Impacts of KUR disbursements on economic sectors in other provinces are very limited.